Cyber-Safety: Concepts, Threats, and Essential Measures - Karim Barbhuiya, Rejaul (Indian Journal of Educational Technology, 2024)
The rapid advancement of technology has led to a digital revolution, impacting various aspects of our lives and elevating the importance of cybersecurity. As society increasingly relies on technology for communication and learning, cybersecurity awareness has become crucial. The COVID-19 pandemic accelerated the adoption of digital tools in education, necessitating a comprehensive approach to address cybersecurity challenges for students and teachers. This research article explores the background and significance of cybersecurity, focusing on evolving cyber threats faced by educational institutions and society. It addresses cyberbullying, misinformation, and fake news, advocating for responsible netizenship and media literacy among students. The study comprehensively examines cyber threats, ranging from malware-based attacks to social engineering and denial-of-service incidents. Emphasising cybersecurity as an integral pillar of the digital age, the research stresses the need for robust strategies to safeguard data, ensure privacy, and create a safe online environment for students, teachers, and the broader community. The study aims to gain insights into the profound impact of cyber threats on individuals and institutions, highlighting the significance of cybersecurity in the digital landscape. Essential measures like user education, device configuration, network security, and identity management are proposed to strengthen defences and secure the digital environment. The paper addresses children’s cyber safety concerns, focusing on combating cyberbullying, misinformation, and scams. It presents effective awarenessraising strategies and preventive measures, emphasising the role of education campaigns and parental involvement. This research strives to safeguard education in the digital age by promoting responsible online behaviour and fostering a secure digital environment. The research contributes to the current initiatives towards cyber safety and security by demonstrating the importance and critical role of awareness in the cyber safety and security strategy of the country. The major contribution is the advancement of the theoretical and practical basis for cyber security awareness in proposing a model framework for developing awareness.